CBDC-MXN: Challenges and Perspectives in The Implementation as a Mexican Digital Currency - Flores Gálvez , Jessica Nallely; Mata Hernández, José Miguel (Mercados y Negocios, 2023)
This research shows a proposal for developing of a Mexican Central Bank Digital Currency by Banco de México. Therefore, a dynamic SWOT matrix is used to present the strengths, weaknesses, opportunities, and threats of the development of the Mexican Central Bank Digital Currency. In addition, an analysis of the stablecoins of the Mexican peso is made to know their landscape and current use, the above making use of Blockchain explorers such as BscScan, Etherscan, Polygonscan, and Tronscan. MMXN, Moneta Digital, is the stablecoin of the Mexican Peso with the most significant number of users and transactions. According to the results obtained, it is shown that the Mexican CBDC is viable, but it must overcome challenges and issues to be implemented and used by the population.